1982
DOI: 10.2307/3898321
|View full text |Cite
|
Sign up to set email alerts
|

Short Duration Grazing at the Texas Experimental Range: Effects on Forage Quality

Abstract: Variation in percent crude protein (% CP) of available forage was examined at the Texas Experimental Ranch as a function of grazing treatment, plant species, physiological age of plant tissue, and season. Results indicate that % CP content varied as much as function of physiological age of plant tissue as a function of plant species. Although quantity of crude protein of total standing crop averaged significantly more in an ungrazed treatment than in a short duration grazing treatment, % CP was generally great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Weather data ( Figure 2) indicated that average monthly temperatures were 2.3°C greater and average monthly precipitation was 10.3 cm less in 2010 than in 2009, which likely resulted in an increase of senescent forage towards the conclusion of yr 2. Frequent defoliation of pasture forage in a managementintensive grazing system has been shown to increase pasture quality when pastures are used before forage senescence (Heitschmidt et al, 1982). Therefore, the reasons for the differences in DM yields in HG pastures between grazing seasons are not clear, but are most likely a result of increased stocking density on HG pastures compared with HO and decreased monthly rainfall in yr 2.…”
Section: Forage Quality Yield and Botanical Compositionmentioning
confidence: 99%
“…Weather data ( Figure 2) indicated that average monthly temperatures were 2.3°C greater and average monthly precipitation was 10.3 cm less in 2010 than in 2009, which likely resulted in an increase of senescent forage towards the conclusion of yr 2. Frequent defoliation of pasture forage in a managementintensive grazing system has been shown to increase pasture quality when pastures are used before forage senescence (Heitschmidt et al, 1982). Therefore, the reasons for the differences in DM yields in HG pastures between grazing seasons are not clear, but are most likely a result of increased stocking density on HG pastures compared with HO and decreased monthly rainfall in yr 2.…”
Section: Forage Quality Yield and Botanical Compositionmentioning
confidence: 99%
“…Rapid movements, sometimes over large distances, are a characteristic behavioral pattern of undomesticated animals that evolved in grassland ecosystems. Experimental livestock management plans implementing animal movement patterns similar to those of the Serengeti ungulates have doubled animal production per unit land area compared with control plots (Walton et al 1981, Heitschmidt et al 1982a) due to enhanced forage quality (Walton et al 1981, Heitschmidt et al 1982b and grassland productivity (Heitschmidt et al 1982c). Deterioration of agricultural grazing lands may be less a consequence of stocking density than of the reduced responsiveness of a confined fauna to the temporal and spatial dynamics of grassland ecosystems.…”
Section: Primary Productivity and Herbivory In A Stochastic Environmentmentioning
confidence: 99%
“…Reference samples of known in vivo digestibility were analyzed in each batch run for standardization of OMD estimates. Forage quality analyses were limited to subsamples collected in the RG treatment because previous research (Heitschmidt et al 1982b) had shown %CP of live and dead tissue of a given species was unaffected by grazing treatment. Subsamples were combined by treatment (RG-14 and RG-42) and time (before and after grazing) prior to qualitative analyses.…”
Section: Vegetdion Hmplingmentioning
confidence: 99%